Reflexões sobre o transe ritualístico no candomblé = Reflections on the ritualistic trance in candomblé - Costa, Alexandre (Ciencias sociales y religión, 2014)
The bodily manifestation of energies or spirits, although order phenomenological bias is an important research regarding the social organization of certain religious groups. This paper presents some observations on the trance mediumship in Candomblé Ketu based on considerations of Roger Bastide, Reginaldo Prandi. Their data are also drawn from ethnographic research in terraces of Candomblé Goiânia metropolitan region and coordinated by the Center for Integrated Studies AfricanAmericas (CieeA - UEG) and Center for Critical Studies and Applied to Religious Discourse (NOUS - UFG). A transdisciplinary perspective of this study is to understand our object not only with his description, but from its discursive construction: it is what is said about it. Therefore, articulate with reading classical studies Africanists some concepts of Foucault and Bakhtin, taking anthropological documents and speeches collected as a set of statements that relate to each other in their network, subjects and fields of knowledge.